Signal -To-Noise Ratio Estimation In Scanning Electron Microscope Imaging System - Sim, Kok Swee (2006)
Two new methods, the Autoregressive(AR) model and the Mixed Lagrange Time Delay Estimation Autoregressive (MLTDEAR) model, are developed to estimate the Signal-to-Noise Ratio (SNR) from a single image for the Scanning Electron Microscope (SEM) Imaging System application.